Pengaruh Manajemen Talenta dan Manajemen Pengetahuan Terhadap Kinerja Pegawai - Rohendi Rohendi; Ading Rahman Sukmara; Aini Kusniawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The problems faced in this study include (1) How does talent management affect employee performance at the BLUD Banjar City General Hospital? (2) How does knowledge management affect employee performance at the BLUD Banjar City General Hospital? (3) How do talent management and knowledge management affect employee performance at the BLUD Banjar City General Hospital? This study aims to study, find out, and analyze (1) The effect of talent management on employee performance at the BLUD Banjar City General Hospital. (2) The effect of knowledge management on employee performance at the BLUD Banjar City General Hospital. (3) The effect of talent management and knowledge management on employee performance at the BLUD Banjar City General Hospital. The method used in this study is an explanatory survey, while the technical data analysis, namely validity test, reliability test, descriptive statistics, Inductive Statistical Analysis with Multiple Regression. The results of the study inform that (1) Talent management has a positive effect on employee performance at the BLUD Rumah Sakti Umum Kota Banjar. This means that if talent management is improved, employee performance at the BLUD Rumah Sakti Umum Kota Banjar will also increase. (2) Knowledge management has a positive effect on employee performance at BLUD Rumah Sakti Umum Kota Banjar. This means that if knowledge management is improved, employee performance at BLUD Rumah Sakti Umum Kota Banjar will also improve. (3) Talent management and knowledge management have a positive effect on employee performance at BLUD Rumah Sakti Umum Kota Banjar. This means that if talent management and knowledge management are improved, employee performance at BLUD Rumah Sakti Umum Kota Banjar will also improve.